Comparing the effectiveness of schema-based and emotionally focused couple therapies on self-differentiation and marital disillusionment in couples in Mashhad - Gole Maryam Nazer; Abolfazl Bakhshipour; Mehdi Ghasemi Motlagh (Social Determinants of Health)
Background: Reducing self-differentiation and marital frustration in couples weakens the marital bond. The aim of the study was to compare the effectiveness of schema-based couple therapy (SBCT) and emotion-focused couple therapy (EFCT) on self-differentiation and marital frustration in couples.